MODELING OF GAS SOLUBILITY IN BRINE - Sorensen H.; Pedersen K.S.; Christensen P.L. (My University, 2002)
Cubic equations of state (EOS) are widely used to represent the phase behavior of gas-oil-systems, whereas different types of models have traditionally been used to describe gas solubility in aqueous mixtures. Since formation water is often produced together with gas and oil, it is also desirable to model gas solubility in formation water using an EOS. It has previously been shown that the mutual solubility of hydrocarbons and pure water can be well represented by a cubic EOS by applying a non-classical mixing rule for the a-parameter. However, formation water produced together with gas and oil will often have a considerable content of salts, which must be accounted for in gas solubility calculations. It is shown that the mixing rule of Huron and Vidal can be stretched to account for the presence of the salts NaCl, KCl and CaCl2 in the water phase. This is done by assigning hypothetical critical properties to the salts, and estimating interaction parameters for gas-salt interactions based on experimental gas solubility data. This model concept gives a fair representation of the gas solubility in salt water.